Patients with Parkinson’s disease need spiritual care - Paal, Piret; Lorenzl, Stefan (Annals of Palliative Medicine, 2019)
In his bestselling book “Being Mortal: Medicine and What Matters in the End” the American surgeon Atul Gawande wrote: “The battle of being mortal is the battle to maintain the integrity of one’s life—to avoid becoming so diminished or dissipated or subjugated that who you are becomes disconnected from who you were or who you want to be.” (1). In palliative care, improving the spiritual dimension of whole person care has been merely an attempt to diminish the feeling of disconnectedness in self(-perception) of the most vulnerable. Attention to spirituality in patients’ with chronic neurological diseases has been remarkably low. Today when palliative care capacity building among all healthcare practitioners caring for patients with chronic illnesses is increasing, and the demand towards maintaining the health- related quality of life has to be met, the interest towards why and how to tap into patients’ and their caregivers’ spiritual needs and resources is growing.